Peningkatan Financial Life Skills Melalui Edukasi Literasi Keuangan Warga Desa Sambirata, Kecamatan Cilongok, Kabupaten Banyumas - Ira Hapsari; Erna Handayani; Mukti Agung Wibowo (Jurnal Pengabdian Kepada Masyarakat Kalam, 2022)
The financial literacy problem in rural communities still lacking significantly impacts community development and empowerment. Cases of illegal loan entanglement that cause family welfare to decline are common in Sambirata Village, Cilongok District, Banyumas Regency, Central Java. This village has great potential but still needs empowerment to develop that potential. This community service is carried out to improve the financial life skills of the Sambirata villagers. Managing finances is increasing financial literacy and growing small businesses to supplement the family income. Seeing the great potential of Sambirata village from its natural beauty, agricultural, and fishery potential, community empowerment in Sambirata Village supports improving the welfare of the residents through further development of tourism, agriculture, and forestry. Low literacy Citizens' finances are the primary focus that must be immediately improved so that the goals of village development can be achieved.